1997
DOI: 10.1111/j.1432-1033.1997.00421.x
|View full text |Cite
|
Sign up to set email alerts
|

Tumor‐Necrosis Factor‐α Modulates Mitogen‐Activated Protein Kinase Activity of Epidermal‐Growth‐Factor‐Stimulated MCF‐7 Breast Cancer Cells

Abstract: Tumor-necrosis factor(TNF)-a inhibited in a dose-dependent fashion the proliferation of epidermalgrowth-factor(EGF)-stimulated MCF-7 breast cancer cells with an IC,, of 0.25 nM. A comparable TNFa-mediated inhibition of ~42144 mitogen-activated protein (MAP) kinase activity was observed in 10 nM EGF-stimulated cells. The MAP kinase activity dropped 50% within 3 min of TNF-a (1 nM) addition to EGF-stimulated MCF-7 cells. EGF and TNF-a, when added independently, led to a transient stimulation of MAP kinase activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 36 publications
3
12
0
Order By: Relevance
“…Interestingly, Erk2 expression levels were higher than Erk1 in most tumor samples (Mueller et al, 2000). Not much is known about the independent functions of Erk2 as opposed to Erk1; however, it has been reported that Erk2 plays a critical role in mediating EGF-stimulated proliferation in MCF-7 breast cancer cells (Flury et al, 1997). The specific downstream effects of Erk1 and Erk2 activation in the mammary epithelial cells are still not defined.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Erk2 expression levels were higher than Erk1 in most tumor samples (Mueller et al, 2000). Not much is known about the independent functions of Erk2 as opposed to Erk1; however, it has been reported that Erk2 plays a critical role in mediating EGF-stimulated proliferation in MCF-7 breast cancer cells (Flury et al, 1997). The specific downstream effects of Erk1 and Erk2 activation in the mammary epithelial cells are still not defined.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous work with the MAP kinases of different organisms, phosphorylation of the threonine and tyrosine residues in the TEY signature of domain VIII of the p42-44 MAP kinase family is necessary for phosphorylation activity. When both residues are dephosphorylated, p42-44 MAP kinases are unable to phosphorylate their substrates (Anderson et al, 1990;Nishida & Gotoh, 1993;Flury et al, 1997). Accordingly, antibodies against the phosphorylated forms of p42-44 MAP kinases are used in many eukaryotic organisms (fungal, mammalian and plant) as indicators of the activation of these MAP kinases.…”
Section: Discussionmentioning
confidence: 99%
“…MAP kinase activity was assayed in 20 l cytosolic fractions using a method (Flury et al, 1997) modified according to a procedure of Clark-Lewis et al (1991). The substrate peptide used consists of 14 amino acids surrounding the Thr 669 phosphorylation site of the epidermal growth factor receptor (EGFR) modified to contain only one phosphorylation site and 2 additional arginines to allow binding to P81 Whatman paper (Amersham, Buckinghamshire, UK) and is specific for p42/44 MAPK (Flury et al, 1997).…”
Section: Map Kinase Measurementsmentioning
confidence: 99%